Making Mediation Law - International Finance Corporation (Washington, DC, 2017)
Mediation is a procedure in which an intermediary without decision-making powers (the mediator) systematically facilitates communication between the parties of a conflict with the aim of enabling the parties themselves to take responsibility for resolving their dispute. Mediation is a highly flexible and adaptable process - a factor that can create challenges for regulators. The goals of this book are to: describe the regulatory landscape of mediation; outline the parameters of a regulatory project about mediation; offer a step-by-step guide to making policy and law about mediation; and generate enthusiasm among a wide range of regulatory stakeholders to become involved in shaping the future of mediation. The introduction sets out the goals and structure of the book before explaining some ideas that inform the approach to the topic. Chapter two offers an international overview of the regulatory landscape that considers the different ways in which people can access mediation. Chapter three commences the regulatory project. Chapter four leads into the next stage of making mediation law, which involves making decisions about the content and regulatory form that one wish to use to regulate various aspects of mediation. Chapter five looks at success factors, pitfalls, and lessons learned. Finally, chapter six provides regulatory topics checklist.